MINDFUL MESSAGING: PUBLIC RELATIONS (PR) STRATEGIES IN SCHOOLS BY USING HIERARCHY OF EFFECTS - Abdullah, Abdullah; Putri, Dinda Febrianti; Herlina, Amalia (Managere: Indonesian Journal of Educational Management, 2024)
This research explores the application of mindful messaging strategies in PR (Public Relations) in schools using the Hierarchy of Effects principle and its impact on communication effectiveness, audience engagement, and school image. Through interviews with various stakeholders such as school principals, financial managers, committee administrators, event coordinators, heads of PR, alums, new students, and parents, as well as collecting data through observation and document analysis, this research identified that message consistency and content relevance is critical. They are influencing emotional connections and audience engagement. The research results show that effective implementation of mindful messaging can improve a school's image and influence new student enrolment decisions, with the effectiveness of communication channels depending on consistent message management and interactive communication techniques. The conclusion of this study emphasizes the importance of planned and emotional communication strategies in strengthening school homework and influencing audience perceptions and behaviour.